Unveiling the black desert cobras: first records of Walterinnesia aegyptia Lataste, 1887 (Serpentes: Elapidae) from Oman and taxonomic revision of the genus Walterinnesia Lataste, 1887 - Carranza, Salvador; Al-Amri, Abdurhman Said; Busaidi, Ahmed Al; Els, Johannes; Estarellas, Maria; Al-Buthari, Rashid; Koppetsch, Thore; Tulloch, Sergi; Saadi, Saleh Al; Al-Rashdi, Said Hamed Ali; Hashmi, Sulaiman Al; Burriel-Carranza, Bernat (Zootaxa, 2025)
N/A